Achieving high strength and ductility in Fe50Mn25Ni10Cr15 medium entropy alloy via Al alloying. (20th February 2022) - Jiang, Zhen; Wei, Ran; Wang, Wenzhou; Li, Mengjia; Han, Zhenhua; Yuan, Shuhan; Zhang, Kaisheng; ChenChen,; Wang, Tan; Li, Fushan
Highlights: (Fe50 Mn25 Ni10 Cr15 )100- x Al x ( x =0–8 at.%) medium-entropy alloys (MEAs) were prepared. x  = 5–7 alloys were mixtures of FCC and BCC phases. The mechanical properties of the x =5 alloy are superior to most of the HEAs and MEAs. The strengthening mechanisms of the x =5 and 7 alloys were clarified. Abstract: The microstructure and tensile properties of (Fe50 Mn25 Ni10 Cr15 )100- x Al x ( x  = 0–8 at.%) medium-entropy alloys (MEAs) were investigated. It was found that the crystalline structure changes from face-centered cubic (FCC) single phase to FCC+ body-centered cubic (BCC) dual-phase with the increase of Al content. Therefore, the addition of Al elements with large atomic size could induce solid solution strengthening and dual-phase heterogeneous structure strengthening. Correspondingly, the present MEAs exhibit excellent combinations of yield strength, ultimate tensile strength (UTS) and ductility both at 298 and 77 K. Among the MEAs, the (Fe50 Mn25 Ni10 Cr15 )95 Al5 alloy has a remarkable combination of cryogenic UTS (1077 MPa) and ductility (~85%), and has lower raw material costs than the reported high-entropy alloys (HEAs) and MEAs. The correlation among microstructure and mechanical properties and the corresponding strengthening mechanism were clarified. Graphical abstract: Image, graphical abstract